Comparing and evaluating an interactive, subject-based search system with the traditional digital library’s search functionality - Kyprianos, Konstantinos (Journal of Integrated Information Management, 2024)
Purpose - The purpose of this paper is to compare and evaluate the usability, usefulness and effectiveness of an Interactive, Information Retrieval – IIR system with a DSpace-based digital library. Design/methodology/approach – The proposed evaluation approach consists of two subcomponents. The first one refers to a log file analysis capable of revealing quantitative features of the systems’ usage. The second part refers to a user survey that compares the new IIR system against the traditional subject-based search functionality provided by DSpace in terms of usefulness and effectiveness. Findings - Based on the evaluation results, it seems that users are very interested in employing new methods and techniques in information seeking and retrieval, especially when such new tools and methods help them in fulfilling their information needs accurately and timely. The results also revealed that the users are more satisfied when employing the new search functionality and the search and retrieval process is improved. Originality/value - A novel IIR system for subject-based browsing was evaluated and interesting results for the future of such tools are shown.